Teacher motivation and teacher effectivenesss as correlates of learning outcome in government among senior secondary schools in Ekiti, Nigeria (2013)
"The quality of education provided in any society and nature of the change effected by that education are both dependent on the motivation of teachers and effectiveness of their teaching in schools. It determines the aspect of life and the world with which the learners are brought into contact. Hence, there is need to look into the motivation and teaching effectiveness of teachers as factors that could affect the learning outcomes of Government as a subject. The study therefore, sought to investigate teacher motivation and teacher effectiveness as correlates of students' learning outcome in SS2 Government among public secondary schools in Ekiti State. Multistage sampling technique was employed to select eighty (80) Government secondary school teachers and eight hundred (800) senior secondary school studentsfrom eighty public secondary schools in eight Local Government Areas in Ekiti state. A total of eight hundred and eighty (880) respondents were used in all. Three instruments were used for the study, namely: Teacher Motivation Questionnaire (TMQ), Teacher Effectiveness Rating Scale (TERS) and Student Achievement Test in Government (SATG) with reliability coefficients of 0.82, 0.83 and 0.79 respectively. Data were analysed using multiple regression. Results offindings show that teacher motivation (Salaries and other Fringe Benefits, Conducive Environment, Advancement on the Job, promotion) and teacher effectiveness had composite contribution to students learning outcome in Government (R= .555; Adjusted R2 = .261; F (5.75) = 6.578; P < .05). It was also found that, there was a positive relative contribution of each factor to the learning outcome in government, alaries and Fringe benefits (β = .227), Conducive Environment (β = .044), Advancement 011 the job (β = .140), promotion (β = .273), and Teacher effectiveness (β = .239). However; it was revealed that, only Salary and Fringe Benefits (β = .277; t = 2.100, P < .05), Promotion (β = .273; t = 2.587, P < .05) and Teacher Effectiveness (β = .239; t = 2.95, P < .05) were the most influential factors that contribute to learningoutcome in Government. It is therefore recommended that school stakeholders should employ different ways of motivating their teachers towards imparting the contents of the curriculum effectively. School Principals should monitor very closely that the strategies employed by the teachers are in accordance with the contents of the school curriculum where the worthy policies of education are written."